Evaluation of the performances of ‘typical’ imaging abnormalities of axial spondyloarthritis: results of the cross-sectional ILOS-DESIR study - Maxime Dougados; Laure Gossec; Anna Molto; Pascal Richette; Marie-Martine Lefèvre-Colau; Violaine Foltz; Romain Beaufort; Jean-Denis Laredo; Philippe Dieude; Philippe Goupille; Antoine Feydy (RMD Open)
Objective To evaluate the prevalence and performance as axial Spondyloarthritis (axSpA) diagnostic feature of radiographic and MRI lesions ‘typical’ of axSpA of the sacroiliac joint (SIJ) and spine in a mechanical chronic back pain (CBP) population and in an axSpA cohort.Methods Cross-sectional multicentre study. Patients: (1) recent onset axSpA (DESIR cohort) and (2) mechanical non-axSpA CBP matched for age and gender (ILOS study). Imaging: radiographs and MR scans were performed identically in both groups. All images were centrally read, blinded for diagnosis and for other imaging findings in the same patient. Statistical analysis: prevalence of lesions ‘typical of axSpA’ were compared in both groups. Sensitivity, specificity and positive likelihood ratios (LR+) of each lesion (and combination of lesions) were calculated.Results A total of 98 patients with CBP were included, and compared with 100 patients with recent onset axSpA. SIJ lesions were consistently more frequent in the axSpA group (35.0% vs 11.8% p<0.001, 35.0% vs 8.4% p<0.001% and 32.0% vs 10.0%. p<0.001 for modified New York criteria, MRI sacroiliitis and ≥3 erosions of the SIJ on MRI, respectively), and performed well (LR+ for ≥3 erosions 3.0 (95% CI 1.6 to 5.8)). Spine lesions were comparable across groups: radiographic lesions were rare, while all MRI lesions were frequent.Conclusion Our study confirms that ‘typical’ lesions can also be observed in patients with non-axSpA CBP but that SIJ lesions by all modalities remain the most valuable for diagnosis, including structural lesions of the SIJ. This suggests the potential interest of adding MRI SIJ structural lesions in the definition of MRI abnormalities for axSpA classification.